NIBP, a Novel NIK and IKKβ-binding Protein That Enhances NF-κB Activation - Hu, Wen-Hui (2005)
The transcription factor NF-κB plays an important role in both physiological and pathological events in the central nervous system. Nevertheless, the mechanisms of NF-κB-mediated regulation of gene expression, and the signaling molecules participating in the NF-κB pathway in the central nervous system are, to date, poorly understood. To identify such molecules, we conducted a yeast two-hybrid screen of a human brain cDNA library using NIK as bait. As a result, we identified a novel NIK and IKKβ binding protein designated NIBP that is mainly expressed in brain, muscle, heart, and kidney. Interestingly, low levels of expression were detected in immune tissues such as spleen, thymus, and peripheral blood leukocytes, where NF-κB is known to modulate immune function. We demonstrated by immunohistochemistry that NIBP expression in the brain is localized to neurons. NIBP physically interacts with NIK IKKβ, but not IKKα or IKKγ. NIBP overexpression potentiates tumor necrosis factor-α-induced NF-κB activation through increased phosphorylation of the IKK complex and its downstream IκBα and p65 substrates. Finally, knockdown of NIBP expression by small interfering RNA reduces tumor necrosis factor-α-induced NF-κB activation, prevents nerve growth factor-induced neuronal differentiation, and decreases Bcl-xL gene expression in PC12 cells. Our data demonstrate that NIBP, by interacting with NIK and IKKβ, is a new enhancer of the cytokine-induced NF-κB signaling pathway. Because of its neuronal expression, we propose that NIBP may be a potential target for modulating the NF-κB signaling cascade in neuronal pathologies dependent upon abnormal activation of this pathway.